Forming Identiy of the Fish-Market Area in Kalanganyar Sidoarjo Through Signage Design - Mohammad Pranoto Soedjarwo; Fairuz Mutia; Lily Syahrial (Nusantara Science and Technology Proceedings)
This research aims to know by designing signage we can form the identity of the fish-market area in Kalanganyar, Sidoarjo. In this research, we used the character appraisal analysis to analyse the existing condition of the fish-market area. This analysis focusing on how to create the signage suitable for increasing the visual identity of the area. Walkthrough analysis was held, to assess whether the pedestrian feels any connections to the feel of the fish market’s signage as an identity of the whole area. Based on the result, the pedestrian majority didn’t feel the visual connectivity to the area, and this can lead to a lack of interest. Pedestrian didn’t feel attracted to the area just by seeing the signage of the existing of that area condition. Pragmatic design approach then used as a way of designing the signage by the area. Using the most famous fisheries product as a branding logo, we use the approachable and funny design of the signage to attract the tourist. By using the same logo and urban design criteria, there are several types of signage that we can apply, for the entire area and the fisheries stall. We used the contrast colour, and summer colour scheme to achieve the most eye-catching signage to establishing the identity of the fish-market area. Besides that, do-it-yourself fisheries accessories added into the façade of the fish stall to reach the identity that we want to create in the fish-market area as the identity of the coastal village fish-market.